2022
DOI: 10.1001/jamanetworkopen.2022.44430
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Behaviors and Prognosis in Patients With Non–Muscle-Invasive Bladder Cancer in the Be-Well Study

Abstract: ImportanceTobacco smoking is an established risk factor associated with bladder cancer, yet its impact on bladder cancer prognosis is unclear.ObjectiveTo examine associations of use of tobacco (cigarettes, pipes, and cigars), e-cigarettes, and marijuana with risk of recurrence and progression of non–muscle-invasive bladder cancer (NMIBC) and to explore use of smoking cessation interventions.Design, Setting, and ParticipantsThe Be-Well Study is a prospective cohort study of patients with NMIBC diagnosed from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
0
11
2
Order By: Relevance
“…5 Kwan, et al also showed that longer duration and more years of smoking behavior will high the risk of bladder cancer recurrence. 6 This also showed in study by Gild, et al in 167 patients with follow up to 15 months, that smoking behavior associated with pathological response to NAC and will be less effective in immunotherapeutics of bladder cancer. 7 Smoking will cause the potential risk of bladder cancer in human.…”
Section: Discussionmentioning
confidence: 80%
“…5 Kwan, et al also showed that longer duration and more years of smoking behavior will high the risk of bladder cancer recurrence. 6 This also showed in study by Gild, et al in 167 patients with follow up to 15 months, that smoking behavior associated with pathological response to NAC and will be less effective in immunotherapeutics of bladder cancer. 7 Smoking will cause the potential risk of bladder cancer in human.…”
Section: Discussionmentioning
confidence: 80%
“…Cancer is becoming increasingly prevalent in middle‐aged and elderly populations and seriously affects life expectancy. Current studies show that many common social life factors, such as smoking, 14 alcohol consumption, 15 and diet, 16 affect the survival of patients with cancer. However, few studies have examined the relevance of socioeconomic factors to the prognosis of patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Patients reported their cigarette smoking history (current, former, never, and pack‐years) at the baseline interview, [ 40 ] along with sociodemographic factors, including age at diagnosis, sex, self‐reported race and ethnicity, marital status, education, household income, current employment status, and body mass index (BMI). Clinical characteristics and treatment information, including tumor size, multiplicity, concomitant Tis, initial transurethral resection of bladder tumor (TURBT), repeat TURBT, perioperative intravesical chemotherapies, and receipt of induction/maintenance Bacillus Calmette–Guérin (BCG) immune therapy, were obtained from the EHR.…”
Section: Methodsmentioning
confidence: 99%